2005
DOI: 10.1002/anie.200500982
|View full text |Cite
|
Sign up to set email alerts
|

F⋅⋅⋅HN Hydrogen Bonding Driven Foldamers: Efficient Receptors for Dialkylammonium Ions

Abstract: Intramolecular F⋅⋅⋅HN hydrogen bonds have been utilized for the first time to construct a new series of foldamers from aromatic amides (see picture; R1=H, Me; R2=CON(n‐C8H17)2). Moreover, the resulting crescent and helical architectures are good acceptors for binding dialkylammonium ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 46 publications
(14 reference statements)
3
81
1
Order By: Relevance
“…11 More recently, we found that this series of folded and related macrocyclic frameworks can stack with fullerenes and coronene more strongly than the (Me)O/H-N hydrogen bonded arylamide counterparts, 12 because the ether methyl groups in the latter system have an important steric hindrance for any intermolecular stacking. Considering that several (Me)O/H-N hydrogen bonding-induced arylamide foldamers have been revealed to assemble into vesicles or organogels in polar organic solvents, 13 we became interested in designing new F/H-N hydrogen bonding-induced foldamers to produce vesicular structures, because the self-stacking of this series of frameworks might be stronger than their (Me)O/H-N hydrogen bonding-induced analogs.…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, we found that this series of folded and related macrocyclic frameworks can stack with fullerenes and coronene more strongly than the (Me)O/H-N hydrogen bonded arylamide counterparts, 12 because the ether methyl groups in the latter system have an important steric hindrance for any intermolecular stacking. Considering that several (Me)O/H-N hydrogen bonding-induced arylamide foldamers have been revealed to assemble into vesicles or organogels in polar organic solvents, 13 we became interested in designing new F/H-N hydrogen bonding-induced foldamers to produce vesicular structures, because the self-stacking of this series of frameworks might be stronger than their (Me)O/H-N hydrogen bonding-induced analogs.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the recognition behavior of linear receptors were reported in 1970s, while Vögtle et al reported the complexing properties of oligo(ethylene glycol) derivatives toward metal ions [6] . More recently, the present authors and Huc et al found that rationally designed hydrogen bonded aromatic amide or hydrazide-based foldamers could bind neutral or ionic guests in more selective manner [7][8][9][10][11][12][13][14][15] , which mainly depends on the size of their cavity, through multiple intermolecular hydrogen bonds. For all the reported oligomers, the presence of a successive network of intramolecular hydrogen bonds forces the backbones to adopt well-predicted folded or helical conformations, which significantly reduces the binding-initiated negative entropy.…”
Section: Introductionmentioning
confidence: 92%
“…Compound 2 was prepared from compounds 14 and 15 [17] by using a procedure similar to that for 1. 1 13 …”
Section: Compoundmentioning
confidence: 99%